From the dance hall to Facebook : teen girls, mass media, and moral panic in the United States, 1905-2010 - Thiel-Stern, Shayla, 1972- (University of Massachusetts Press, 2014)
"In From the Dance Hall to Facebook, Shayla Thiel-Stern takes a close look at several historical snapshots, including working-class girls in dance halls of the early 1900s; girls' track and field teams in the 1920s to 1940s; Elvis Presley fans in the mid-1950s; punk rockers in the late 1970s and early 1980s; and girls using the Internet in the early twenty-first century. In each case, issues of gender, socioeconomic status, and race are explored within their historical context. The book argues that by marginalizing and stereotyping teen girls over the past century, mass media have perpetuated a pattern of gendered crisis that ultimately limits the cultural and political power of the young women it covers."--Publisher's description.